Synthesis of Biphasic Calcium Phosphate and its Behaviour in Simulated Body Fluid - X.V Bui; T.D Thang (Universitas Gadjah Mada, 2016)
The main goal of this study is to elaborate and evaluate the physicochemical properties of the synthetic biphasic calcium phosphate (BCP) powder: an associate compound of hydroxyapatite (HA): Ca10(PO4)6(OH)2 and beta-tricalcium phosphate (?-TCP): Ca3(PO4)2. The new compound BCP has two advantages: high bioactivity (HA) and fast biodegradation (?-TCP). The obtained powder of BCP was prepared by the precipitate method. XRD analysis confirmed the synthetic material contained both HA and ?-TCP crystalline phases. SEM images showed that the small particles of HA attached to bigger particles of ?-TCP in the structure morphology of BCP. The in vitro experiment was carried out in static condition by soaking of a series of 50 mg BCP powder in 100 ml of simulated body fluid solution at different period of soaking time. The XRD and SEM methods studied the microstructureand chemical bond after soaking. The obtained results confirmed the bioactivity of synthetic BCP material by the formation of a new apatite layer on its surface.